PENGARUH MOTIVASI DAN KEPUASAN KERJA KARYAWAN TERHADAP KINERJA KARYAWAN HOTEL DI KAWASAN LOVINA, KABUPATEN BULELENG - Ida Ayu Agung Ngurah Indrawati (Jurnal Ilmiah Hospitality Management, 2016)
Employee satisfaction totally cannot be separated from the fact that employee satisfaction can be achieved when all goals can be fulfilled in performing the duties. Motivation of employees in an organization can be considered either simple or complex problem since humans are basically easy to get motivated by giving what to be desire. The purpose of this study was to identify the effect of work motivation upon employee performance in star-hotels in the area of Lovina, Buleleng and identify the effect of job satisfaction on employee performance in star hotels in the area of Lovina, Buleleng.This research area is located in Lovina, Buleleng. The samples used in this study were 97 employees coming from of three, four, and five stars - hotel in Buleleng, Lovina. Multiple linear regression method was used to explain the pattern of the relationship between the factors of individual character, the perception of fairness, and performance.Based on the results of data statistical calculations on the influence of work motivation and job satisfaction on employee’s performance, it showed that motivation and job satisfaction simultaneously influenced the employee’s performance in stars – hotels in Lovina, Buleleng; partially work motivation and job satisfaction variables affected the performance of employees at the stars - hotels in the heart of Lovina Buleleng; as well as the dominant influence on the motivation of the employee's performance in the area of Lovina, Buleleng.